Interleukin 1 inhibits insulin secretion from isolated rat pancreatic islets by a process that requires gene transcription and mRNA translation. - Hughes, J H (1990)
Recombinant human IL 1 beta inhibits glucose-induced insulin secretion from isolated pancreatic islets and from purified beta-cells obtained by fluorescence-activated cell sorting (FACS) of dispersed islet cells. Brief (1 h) exposure of isolated islets to IL 1 produces sustained inhibition of insulin secretion for at least 17 h after the IL 1 has been removed from the culture medium. An inhibitory effect of IL 1 on insulin secretion is not observed when islets are coincubated with an inhibitor of DNA transcription (actinomycin D). This finding indicates that the inhibitory effect of IL 1 on insulin secretion requires transcription of one or more genes during the first hour of exposure of islets to IL 1. The inhibitory effect of IL 1 on insulin secretion also requires mRNA translation, because three structurally distinct inhibitors of protein synthesis (cycloheximide, anisomycin, and puromycin) prevent IL 1-induced inhibition of insulin secretion when added to islets after the 1-h exposure to IL 1. Two-dimensional gel electrophoresis of islet proteins metabolically labeled with [35S]methionine demonstrates that IL 1 augments the expression of a 65-kD (pl approximately 6.5) protein by greater than 2.5-fold. These findings indicate that biochemical events occurring within 1 h of exposure of islets to IL 1 lead to an inhibition of insulin secretion that persists for at least 17 h after the removal of IL 1. One of the early biochemical effects of IL 1 on islets is gene transcription (0-1 h), which is followed by mRNA translation (after 1 h). Our results suggest that the inhibitory effect of IL 1 on insulin secretion is mediated by protein(s) whose synthesis is induced by IL 1.